2018
DOI: 10.1111/famp.12381
|View full text |Cite
|
Sign up to set email alerts
|

A Culturally Adapted Intervention for Mexican‐Origin Parents of Adolescents: The Need to Overtly Address Culture and Discrimination in Evidence‐Based Practice

Abstract: Latino/a populations in the United States are negatively impacted by widespread mental health disparities. Although the dissemination of culturally relevant parent training (PT) programs constitutes an alternative to address this problem, there is a limited number of efficacious culturally adapted PT prevention interventions for low-income Latino/a immigrant families with adolescents. The current manuscript describes the level of acceptability of a version of the GenerationPMTO intervention adapted for Latino/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 43 publications
4
51
0
Order By: Relevance
“…First, the initial component, embracing the dream, is focused on the need to ground the parenting intervention according to the immigrant experiences that are most salient to parents. Specifically, our cultural adaptation studies have indicated the critical importance of framing the intervention according to the harsh realities of oppression that parents face as immigrants, as well as the motivations they embrace that help them cope with the various forms of adversity that they experience (Parra-Cardona et al, 2016, 2018). Subsequent components are situated according to the theoretical premises of the GenerationPMTO intervention.…”
Section: Healing Through Parenting: An Integrative and Applied Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the initial component, embracing the dream, is focused on the need to ground the parenting intervention according to the immigrant experiences that are most salient to parents. Specifically, our cultural adaptation studies have indicated the critical importance of framing the intervention according to the harsh realities of oppression that parents face as immigrants, as well as the motivations they embrace that help them cope with the various forms of adversity that they experience (Parra-Cardona et al, 2016, 2018). Subsequent components are situated according to the theoretical premises of the GenerationPMTO intervention.…”
Section: Healing Through Parenting: An Integrative and Applied Modelmentioning
confidence: 99%
“…We refer the reader to the original reports of the cultural adaptation studies, which include detailed descriptions of adaptations to curricula according to type of target family (i.e., families with young children vs. adolescents), details of the research designs, and quantitative and qualitative findings from the randomized controlled trials (Parra-Cardona et al, 2012, 2016, 2017a, 2018). …”
Section: Healing Through Parenting: An Integrative and Applied Modelmentioning
confidence: 99%
See 3 more Smart Citations